Impaired oculo-motor behaviour affects both reading and scene perception in neglect patients. (April 2015) - Primativo, Silvia; Arduino, Lisa S.; Daini, Roberta; De Luca, Maria; Toneatto, Carlo; Martelli, Marialuisa
Abstract: Unilateral spatial neglect (USN) is a common neuropsychological disorder following a right-sided brain lesion. Although USN is mostly characterized by symptoms involving the left hemispace, other symptoms are not left lateralized. Recently, it was shown that patients with neglect dyslexia, a reading disturbance that affects about 40% of USN patients, manifest a non-lateralized impairment of eye movement behaviour in association with their reading deficit when they read aloud and perform non-verbal saccadic tasks (Primativo et al., 2013 ). In the present paper, we aimed to demonstrate that the eye movement impairment shown by some USN patients reflects a more general oculo-motor disorder that is not confined to orthographic material, the horizontal axis or constrained saccadic tasks. We conjectured that inaccurate oculo-motor behaviour in USN patients indicates the presence of a reading deficit. With this aim we evaluated 20 patients, i.e ., 10 right-sided brain-damaged patients without neglect and 10 patients affected by USN. On the basis of the patients' eye movement patterns during a scene exploration task, we found that 4 out of the 10 USN patients presented an abnormal oculo-motor pattern. These same four patients (but not the others) also failed in performing 5 different saccadic tasks and produced neglect dyslexia reading errors in both single words and texts. First, we show that a large proportion of USN patients have inaccurate eye movement behaviour in non-reading tasks. Second, we demonstrate that this exploratory deficit is predictive of the reading impairment. Thus, we conclude that the eye movement deficit prevents reading and impairs the performance on many other perceptual tests, including scene exploration. The large percentage of patients with impaired eye-movement pattern suggests that particular attention should be paid to eye movement behaviour during the diagnostic phase in order to program the best rehabilitation strategy for each patient. Highlights: We investigated in detail the eye movement pattern in Unilateral spatial neglect (USN) patients. A large proportion of USN patients show inaccurate eye movement behaviour. The eye movement disorder of USN patients is not left lateralized. The oculo-motor pattern in scene exploration predicts reading abilities in USN patients. Individual detailed screening tests are needed to uncover the eye-movement disorder.